A Review on Sproles & Kendall's Consumer Style Inventory (CSI) for Analyzing Decision Making Styles of Consumers - Jain, Ruby; Sharma, Arti (Indian Journal of Marketing, 2013)
The purchase of goods or services includes a number of factors that affect decision making. Kotler's model of purchase process incorporates five stages that are Need recognition, Information search, Evaluation of alternatives, Purchase decision and Post purchase behavior. Among these, the consumer purchase decision making is more complex and even more important for consumers today than it was in the past. Marketers often seek to learn how and why people shop, this insight helps them to produce and package their products accordingly and be competitive in global terms. To profile an individual's decision style, Sporles and Kendall in 1986 developed a Consumer Style Inventory (CSI), based on the consumer characteristic approach, which focuses on different cognitive dimensions of consumer decision making. They tested it on American female student groups, further retested it, and came out with eight characteristics. Since then, CSI has been extensively tested on consumers of different countries by different researchers. The objective of the paper is to review the different studies conducted since 1986 to 2010 so that further research can get some direction and can contribute significantly to academia and marketers as well. The studies are classified as those conducted in developed countries, countries with emerging economies and those drawing inputs from both. After reviewing the studies, it seems that five characteristics are indispensable to all consumers irrespective of country, gender, age, culture and religion. These are : High quality conscious consumer, Brand conscious price equals quality consumer, Recreational/Hedonistic consumer, Price conscious value for money consumer, and Confused by over choice consumer. Hence, it was concluded that Sproles and Kendall's inventory can be very well used as a basic model.